Real-Time Cyber-Physical Digital Twin for Low Earth Orbit Satellite Constellation Network Enhanced Wide-Area Power Grid - Tianshi Cheng; Tong Duan; Venkata Dinavahi (IEEE Open Journal of the Industrial Electronics Society)
Low Earth orbit (LEO) satellite networks, such as SpaceX's Starlink, offer enhanced communication potential for contemporary power grid measurement and control. Yet, the dynamic nature of these networks complicates their modeling and simulation. This study introduces a modular, data-oriented digital twin framework for real-time simulation of wide-area ac–dc grids with LEO satellite networks. The framework integrates RustSat for satellite tracking, SatSDN with MiniNet for SDN simulations, and entity-component-system (ECS)-Grid for real-time power system simulation. It features a data-centric design using an ECS framework with a structure-of-arrays memory layout, optimizing cache efficiency and computational performance, and offers high extensibility for interdisciplinary simulations. This marks the initial effort to develop a digital twin for real-time co-simulation of large-scale power systems and LEO satellite constellation networks. Evaluations on a wide-area synthetic ac–dc system with multiple satellite network types confirm the efficiency and precision of our approach, underscoring its potential in bridging LEO satellite networks with power system applications.